2022
DOI: 10.1093/molbev/msac076
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Signatures of Selection Before and After European Colonization in Latin Americans

Abstract: Throughout human evolutionary history, large-scale migrations have led to intermixing (i.e., admixture) between previously separated human groups. Although classical and recent work have shown that studying admixture can yield novel historical insights, the extent to which this process contributed to adaptation remains underexplored. Here, we introduce a novel statistical model, specific to admixed populations, that identifies loci under selection while determining whether the selection likely occurred post-ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 103 publications
(208 reference statements)
1
29
0
Order By: Relevance
“…This method is a modification of the admixture-aware linear model-based test developed by Mathieson et al (2015) ; however, our test is specifically designed for two population admixture scenarios. AIMLESS is similar to other likelihood ratio test (LRT)-based tests ssuch as AdaptMix ( Mendoza-Revilla et al 2021 ) and Ohana ( Cheng et al 2022 ) but does not rely on a priori ancestry estimation and determines the mixture components for the ancestries considered for each single-nucleotide polymorphism (SNP) independently instead of using a genome-wide estimate.…”
Section: New Approachesmentioning
confidence: 99%
“…This method is a modification of the admixture-aware linear model-based test developed by Mathieson et al (2015) ; however, our test is specifically designed for two population admixture scenarios. AIMLESS is similar to other likelihood ratio test (LRT)-based tests ssuch as AdaptMix ( Mendoza-Revilla et al 2021 ) and Ohana ( Cheng et al 2022 ) but does not rely on a priori ancestry estimation and determines the mixture components for the ancestries considered for each single-nucleotide polymorphism (SNP) independently instead of using a genome-wide estimate.…”
Section: New Approachesmentioning
confidence: 99%
“…These low-frequency functional variants are considered to be in the process of being eliminated from the population by negative selection (Gibson, 2018; Lettre, 2014; Zeng et al, 2018). Nevertheless, an increasing number of studies are showing that more complex evolutionary histories (Benton et al, 2021; Mathieson & Mathieson, 2018), including introgression from archaic hominins (McArthur et al, 2020), geography-specific adaptation (Hamid et al, 2021; Lachance & Tishkoff, 2013; Mendoza-Revilla et al, 2021), negative selection (Zeng et al, 2018), and polygenic selection (Barghi et al, 2020; Berg & Coop, 2014; Pritchard et al, 2010; Sella & Barton, 2019) may explain the allele frequencies of variants associated with complex diseases. In this context, we aim to test the hypothesis that balancing selection is a considerable force in shaping the allele frequencies of extant functional deletions in the human genome.…”
Section: Introductionmentioning
confidence: 99%
“…The recency of colonization may thus mask the detection of selected genomic regions (Schrider and Kern, 2017;Vargas et al, 2022). While recent analyses have identified selection signals possibly linked to colonization by modeling allele frequency deviations considering admixture, the candidate loci exhibit very large selection coefficients (~0.15-0.2) that enhance statistical power (Zheng and Wiehe, 2019;Mendoza-Revilla et al, 2022). Taking these limitations into account, pathogen-driven selection acting on post-contact immunity genes in Indigenous peoples of the Americas would thus be best identified by population genetic methods that can detect soft selective sweeps, comparisons between ancient and contemporary genomes, comparisons between worldwide populations, and polygenic approaches, wherein selection signals are observed cumulatively across immune gene classes and pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating admixed Latin American populations in Colombia, Mexico, Peru, and Puerto Rico suggested that selection may have acted upon admixed alleles from Africa, particularly within the HLA region and in pathways involved in inflammation, such as the innate and adaptive immune response (Norris et al, 2020). Another study on five Latin American cohorts showed that HLA alleles under putative selection carry an overrepresentation of African ancestry (Ongaro et al, 2021;Mendoza-Revilla et al, 2022). This study used deviations from neutrality in the expected allele frequency in admixed populations, given known allele frequencies in the source populations, to allow detection of selected regions despite high levels of admixture.…”
Section: Genetic Studies Investigating European and African Admixed A...mentioning
confidence: 99%